SANOAT KORXONALARI INVESTITSIYA SALOHIYATINI KUCHAYTIRISHDA FAOLIYATNI DIVERSIFIKATSIYALASH MEXANIZMLARI (Marketing Journal, 2026)
AbstractThe article analyzed the mechanisms of activity diversification in increasing theinvestment potential of industrial enterprises. The study examined the economicessence of diversification and its impact on financial stability, risk distribution, and cash flow stabilization. Based on the example of oil and fat industry enterprises, therole of product and raw material diversification in enhancing investment attractivenesswas assessed. Internal resources and external factors were systematized through SWOTanalysis. The findings demonstrated that diversification decisions based on economiccalculations, market analysis, and risk assessment contributed to strengthening theinvestment potential of enterprises.Keywords: diversification, investment potential, investment attractiveness,strategic management, risk management, financial stability, innovative development,synergy effect, capital attraction, enterprise value, portfolio theory